2011
DOI: 10.1007/s10611-011-9277-6
|View full text |Cite
|
Sign up to set email alerts
|

Computer says no: technology and accountability in policing traffic stops

Abstract: The Road Traffic Act 1988

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…This is the result of both routine police checks and 'crackdown' operations. The process uses Automatic Number Plate Recognition (ANPR) to cross-check vehicles against the Police National Computer, which is linked to the Motor Insurance Database and the Driver and Vehicle Licensing Agency, automatically cross-checking licence and insurance records (Kinsella and McGarry, 2011). Skolnick also refers to traffic policing as an example of the mass production of penalties.…”
Section: Conceptualising Automated Policingmentioning
confidence: 99%
“…This is the result of both routine police checks and 'crackdown' operations. The process uses Automatic Number Plate Recognition (ANPR) to cross-check vehicles against the Police National Computer, which is linked to the Motor Insurance Database and the Driver and Vehicle Licensing Agency, automatically cross-checking licence and insurance records (Kinsella and McGarry, 2011). Skolnick also refers to traffic policing as an example of the mass production of penalties.…”
Section: Conceptualising Automated Policingmentioning
confidence: 99%
“…First, road/traffic policing is a clear example of the trend towards collapsing the distinction between ‘high’ and ‘low’ policing (Brodeur, 2007) in the context of the increasing use of surveillance technologies to facilitate essential but mundane policing functions (Goldsmith, 2005; Kinsella and McGarry, 2011; Wells, 2007, 2008). Second, traffic policing is one of the routine encounters between the public and criminal justice agencies that has significant potential to impact adversely on public confidence in criminal justice (Goldsmith, 2005; Hinds, 2009; Kinsella and McGarry, 2011; Neyroud and Disley, 2008; Wells, 2007, 2008, 2011). As Goldsmith, (2005: 452) argues:Enforcing traffic laws even in democracies poses a particular challenge for public trust in police.…”
Section: Everyday Surveillance and The ‘Misuse’ Of Technology?mentioning
confidence: 99%
“…The public (and media) response to the implementation of a camera-based system for monitoring vehicles highlights several problems with the criminal justice ‘techno-fix’. Within a relatively short period of time, public confidence in this surveillance system as a mechanism for making roads ‘safer’ began to show a marked decline, to be replaced with a growing popular perception that speed cameras were simply being used to generate income from law-abiding motorists (see, for example, Daily Telegraph , 2010a), and that number plate recognition technology used to trap ‘irresponsible’ drivers was being used inflexibly and unfairly, to the detriment of ‘normal’ drivers (Kinsella and McGarry, 2011). In their review of research into public attitudes to speed cameras, Gains et al (2005: 66) found that between 1999 and 2004 the percentage of respondents in the UK who agreed with the statement ‘cameras are an easy way of making money out of motorists’ rose nationally from 45 per cent to 55 per cent, but in some regions of the UK rose to over 70 per cent.…”
Section: Everyday Surveillance and The ‘Misuse’ Of Technology?mentioning
confidence: 99%
See 2 more Smart Citations